PENGARUH RETURN ON ASSET, RISIKO SISTEMATIK, VOLUME PERDAGANGAN SAHAM, BID-ASK SPREAD, DAN VOLATILITAS SAHAM TERHADAP RETURN SAHAM (Studi Kasus Pada Perusahaan Jakarta Islamic Index Tahun 2015-2020) - Cindy Oginia Bertischa Putri; Muhamad Syaichu (Diponegoro Journal of Management, 2023)
ABSTRACT One of the instruments in the capital market that until now is most in demand by investors is the stock instrument. Stocks provide attractive benefits for investors in the form of capital gains. One of the motivating factors for an investor to make an investment is the stock return value obtained. This study aims to determine the effect of return on assets (ROA), systematic risk, stock trading volume, bid-ask spread, and stock volatility on stock returns. In this study, a purposive sampling technique was used to take samples of companies with criteria including companies listed on the Jakarta Islamic Index (JII) in the 2015-2020 period, there were data from financial reports from the variables in this study, namely return data. on assets (ROA), systematic risk, stock trading volume, bid-ask spread, stock volatility, and stock returns during the research observation period. Based on the results of the analysis that has been done, it can be concluded that partially systematic risk variables, stock trading volume, bid-ask spread have a positive and significant effect on stock returns. While the research results are different from the variable return on assets (ROA) which has a positive and insignificant effect on stock returns, while the results of stock volatility have a negative and insignificant effect on stock returns. Simultaneously return on assets (ROA), systematic risk, stock trading volume, bid-ask spread, and stock volatility have a significant influence on stock returns with a significance value of 0.000. The magnitude of the ability to explain the dependent variable given by the five independent variables is 44.8%